Skeletal development is regulated by fibroblast growth factor receptor 1 signalling dynamics. - Hajihosseini, M; Lalioti, MD; Arthaud, S; Burgar, H; Brown, J; Twigg, SR; Wilkie, A; Heath, J (2004)
Ligand-dependent signalling pathways have been characterised as having morphogen properties where there is a quantitative relationship between receptor activation and response, or threshold characteristics in which there is a binary switch in response at a fixed level of receptor activation. Here we report the use of a bacterial artificial chromosome (BAC)-based transgenic system in which a hypermorphic mutation has been introduced into the murine Fgfr1 gene. These mice exhibit cranial suture and sternal fusions that are exacerbated when the BAC copy number is increased. Surprisingly, increasing mutant BAC copy number also leads to the de novo appearance of digit I polydactyly in the hind limb and transformations of the vertebrae. Polydactyly is accompanied by a reduction of programmed cell death in the developing hind limb. Candidate gene analysis reveals downregulation of Dkk1 in the digit I field and upregulation of Wnt5a and Hoxd13. These findings show that Fgfr1-mediated developmental pathways exhibit differing signalling dynamics, whereby development of the cranial sutures and sternum follows a morphogen mode, whereas development of the vertebral column and the hind limbs has threshold signalling properties.